3D mapping direction Universiti Malaysia Pahang campus Gambang - Tines Kumar, Ponniah (2014)
At present, all universities in Malaysia only use the map to the destination as a 2D map as know as sign board. This is because all of the university campus is big campus and all the buildings or faculty positions are very far from one to one building on the other. Besides the increased cost to put signage on buildings. So, not all users of this 2D signage can reach to their destination building To solve this problem, I intend to provide a kiosk machine with 3D mapping system Direction at University Malaysia Pahang Campus Gambang